A lattice-based linkable ring signature supporting stealth addresses - Liu, Zhen (2020)
First proposed in CryptoNote, a collection of popular privacy-centric cryptocurrencies have employed Linkable Ring Signature and a corresponding Key Derivation Mechanism (KeyDerM) for keeping the payer and payee of a transaction anonymous and unlinkable. The KeyDerM is used for generating a fresh signing key and the corresponding public key, referred to as a stealth address, for the transaction payee. The stealth address will then be used in the linkable ring signature next time when the payee spends the coin. However, in all existing works, including Monero, the privacy model only considers the two cryptographic primitives separately. In addition, to be applied to cryptocurrencies, the security and privacy models for Linkable Ring Signature should capture the situation that the public key ring of a signature may contain keys created by an adversary (referred to as adversarially-chosen-key attack), since in cryptocurrencies, it is normal for a user (adversary) to create self-paying transactions so that some maliciously created public keys can get into the system without being detected . In this paper, we propose a new cryptographic primitive, referred to as Linkable Ring Signature Scheme with Stealth Addresses (SALRS), which comprehensively and strictly captures the security and privacy requirements of hiding the payer and payee of a transaction in cryptocurrencies, especially the adversarially-chosen-key attacks. We also propose a lattice-based SALRS construction and prove its security and privacy in the random oracle model. In other words, our construction provides strong confidence on security and privacy in twofolds, i.e., being proved under strong models which capture the practical scenarios of cryptocurrencies, and being potentially quantum-resistant. The efficiency analysis also shows that our lattice-based SALRS scheme is practical for real implementations.